Contemporary global trends in choreographic art development at the beginning of the 21st century - Dmytro Bazela; Tetiana Pavliuk; Olha Babych; Nataliya Batieieva; Petro Kyzim (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.